2018
DOI: 10.1016/j.disc.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Maximum weight stable set in (P7, bull)-free graphs and (S1,2

Abstract: We give a polynomial time algorithm that finds the maximum weight stable set in a graph that does not contain an induced path on seven vertices or a bull (the graph with vertices a, b, c, d, e and edges ab, bc, cd, be, ce). With the same arguments with also give a polynomial algorithm for any graph that does not contain S1,2,3 or a bull.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In this paper, we show that for (S 1,2,4 ,triangle)-free graphs, MWIS can be solved in polynomial time. This generalizes the polynomial-time result for MWIS on (P 7 ,triangle)-free graphs [7] (which was extended by Maffray and Pastor [15] showing that MWIS can be solved in polynomial time for (P 7 ,bull)-free graphs; in the same paper, they also showed that MWIS can be solved in polynomial time for (S 1,2,3 ,bull)-free graphs).…”
Section: Introductionsupporting
confidence: 80%
“…In this paper, we show that for (S 1,2,4 ,triangle)-free graphs, MWIS can be solved in polynomial time. This generalizes the polynomial-time result for MWIS on (P 7 ,triangle)-free graphs [7] (which was extended by Maffray and Pastor [15] showing that MWIS can be solved in polynomial time for (P 7 ,bull)-free graphs; in the same paper, they also showed that MWIS can be solved in polynomial time for (S 1,2,3 ,bull)-free graphs).…”
Section: Introductionsupporting
confidence: 80%
“…More tractability results can be obtained if we put some additional restrictions on the instance graph, e.g., by forbidding more induced subgraphs [6,19,28,33,34,36]. A slightly different direction was considered by Lozin, Milanič, and Purcell [31], who proved that for every fixed t, MWIS is polynomial-time solvable in subcubic S t,t,1 -free graphs.…”
Section: Introductionmentioning
confidence: 99%
“…The class of Triangle-free has been considered in the context of similar previous manuscripts on other subclasses of Triangle-free graphs, namely, on (P 7 ,Triangle)free graphs [7] − see [27] for an extension of this result − and more generally on (S 1,2,4 ,Triangle)-free graphs [9]. However let us observe that Lozin's conjecture is open also for those S i,j,k -graphs for any fixed indices i, j, k which in addition are Triangle-free − recalling that WIS remains NPhard for Triangle-free graphs − that is for restricted and more studied graph classes.…”
Section: Introductionmentioning
confidence: 99%